Manajemen Pelayanan Keamanan Masyarakat Berbasis IT Guna Menjaga Stabilitas Keamanan Dan Ketertiban Masyarakat (Program Panic Button on hand POLRES Malang Kota) - Decky Hendarsono* (Airlangga Development Journal, 2017)
The  increasing number of crimes forces the  need for  security to be  the  main thing and  is  an  important requirement for  humans to  run  daily activities. This study aims to  analyze and  describe efforts to  optimize community service programs in  the  field of IT-based  community   service   in Malang   City  Police.  The research   method   used   is    qualitative,   with   interview   data collection techniques and observation. The  results of  the  study were discussed using two   concepts, namely the  first   question regarding  management  of   IT-based  community  services  in Malang City Police, where those measured using the  concept of POAC   (planning,   organizing,   controling,   actuating). Meanwhile,  the   second  question  discussed  about  efforts  to optimize the  management of public security services in the  field of   IT-based  community  security  uses  the   4m   concept  (man, money, material and  method).